2022
DOI: 10.1002/aoc.6979
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the color change of the solutions of Cp2TiCl upon addition of water

Abstract: Reduction of red bis (cyclopentadienyl)titanium (IV) dichloride (Cp 2 TiCl 2 ) with manganese dust in dry THF produces a green solution that turns deep blue upon the addition of traces of water. Mass spectrometric analysis and DFT calculations have been performed to achieve a better understanding of the species that may be present after the interaction of water with reduced Cp 2 TiCl 2 . The deep blue solution provides a handy visual indicator for the qualitative determination of water in THF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…In tetrahydrofuran (THF) or toluene, the Cp 2 TiCl solution is lime green. However, it turns dark blue when water is added to the solution [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In tetrahydrofuran (THF) or toluene, the Cp 2 TiCl solution is lime green. However, it turns dark blue when water is added to the solution [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Initially, aqua complex 5 was proposed as a HAT reagent (pathway A, Scheme 5) [17]. However, after extending and refining the theoretical calculations, studies of cyclic voltammetry, mass spectrometric analysis, and electro-paramagnetic resonance techniques suggested that aqua complex 6 is the active HAT reagent (pathway B, Scheme 5) [25,28]. Water as a HAT reagent was rigorously demonstrated in the transannular cyclization of caryophyllene oxide 7 (Scheme 6) [24].…”
Section: Carbon-centered Radical Intermediatesmentioning
confidence: 99%
See 1 more Smart Citation